Games, actions and social software: Multidisciplinary aspects - Verbrugge, Rineke; Eijck, Jan (Lecture Notes in Computer Science, 2012)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information, this book collects a set of chapters of the multi-disciplinary project "Games, actions and Social software" which was carried out at the Netherlands Institute for Advanced Study in the Humanities and Social Sciences (NIAS) in Wassenaar, from September 2006 through January 2007. The chapters focus on social software and the social sciences, knowledge, belief and action, perception, communication, and cooperation.